Half nelson [videorecording (DVD)] - Fleck, Ryan, 1976-; Gosling, Ryan, 1980-; Epps, Shareeka; Mackie, Anthony, 1978- (Sony Pictures Home Entertainment, 2007)
A high school teacher with a drug habit finds a friendship in an unlikely source - one of his troubled students. Will their relationship help them or harm them?